Weather, Timing, and Promotions in Minor League Baseball: An Examination of Attendance in the International League - Steven M. Howell; David B. Klenosky; Chad D. McEvoy (Journal of Applied Sports Management, 2015)
Understanding the different factors that impact attendance at sporting events is a timely and relevant topic for researchers and practitioners alike. The present study examines the effects of different types of promotions, weather, and selected temporal elements on attendance in Minor League Baseball. Using data for teams participating in the International League during the 2010 season, results from a multiple regression analysis revealed that special events, promotional giveaways, and non-workdays have a positive impact on attendance; while suboptimal weather conditions have a negative impact. These findings contribute to our understanding of the factors that impact attendance in professional baseball and hold useful implications for future research and managerial practice.
Keywords: minor league baseball; attendance; promotions; weather; timing